KAJIAN YURIDIS PERWAQAFAN TANAH DAN KEABSAHAN PERTUKARANNYA - Arifin Abdullah (Universitas Islam Negeri Ar-Raniry, 2018)
The application of waqf originally rated to immovable things or properties The properties donation and the corporate to be waqf of land (donation for religious or community use) which will become public properties should be based on the Islamic law in accordance with The Quran in al-Baqarah letter from 215 verse, the land which has been waqf should be correspondent to the waqf land declare. In article 3 of law number 41 of 2004 regarding the waqf land in states â€œthe waqf of land which has been officially declared in Islamic way cannot be cancelledâ€, and cannot be changed if the wakif declare it for a certain use. However, the exchange use of the waqf property is not based on the traditional regulation. The objective of this research is to find out explain the implementation of waqf of land based on the prevailing laws, to explain the waqf of land for certain use which can and cannot be changed with other object, and to explain the law about the waqf of land which can be changed. The method used in this research is a normative and sociologic juridicial method in which the writer should study laws and regulations which are relevant to the research, the normative approach is the study of library material including primary, secondary and tertiary materials. The sociologic juridicial opproach is used to study the positive law.